Depression, anxiety and stress among nurses providing care to the COVID-19 patients in province 1. - Bhandari, Menuka (2021)
SUMMARY: COVID-19 pandemic has the potential to significantly affect the mental health of healthcare workers, who stand in the front line of this crisis. Addressing adequately the mental health needs during and after COVID-19, as well as preparation for possible future outbreaks, requires and understanding of the nature and extent of mental health impacts, factors related to negative mental health outcomes and symptoms of mental illness . Descriptive Cross sectional research design was used to identify the level of depression, anxiety and stress among nurses involved in care of COVID-19 patients and to find out the association of selected demographic variables with depression, anxiety and stress. The self- administered questionnaire was used for data collection. The study was conducted in three COVID dedicated hospitals of province 1, namely Koshi COVID Treatment centre, Biratnagar, BPKIHS Dharan and Nobel Medical College, Teaching Hospital Biratnagar. Majority of nurses were belongs to the age less than 25 years and more than half were completed PCL nursing and 80% belonged to staff nurses. Study has revealed that majority of nurses 66.1% (199) were extremely concerned with personnel protective Equipments (PPE), 61.8% staff quarantine then other COVID related variables. The study found that 34.55% nurses have seen mild depression, 45.84% have moderate depression, depression, 13% have severe depression and only 0.99% have extreme depression according to their response, Similarly 8.97% nurses have mild anxiety, 43.18% have moderate anxiety, 33.55% have severe anxiety and 10.63% have extreme anxiety, Regarding the stress, 35.54% nurses have mild stress, 12.29% have moderate stress and 1.99% have severe stress. The study has shown the strong positive correlation among depression, anxiety and stress score. The depressive symptoms were higher among unmarried nurses compared to married nurses (B=0.290, CI=95%, p=0.029). No significant association was observed by age, education, position, experience, marital status and type of hospital with the anxiety among nurses. The stress was higher in axullary nurse mid wife (ANM) than staff nurse (B=0.634, CI=95%, P=0.033). Further the stress symptoms among nursing officer were negatively correlated compared with staff nurses (B=-0.397, CI=95%, P=0.033). To improve the mental health and well being of the nurses, multi-disciplinary interventions, dedicated counseling should be arranged to support the psychological well-being of nurses to help improve their morale. Key Words: anxiety, COVID-19,dedicated hospitals, depression, nurses selected variables, stress